Building measurement - Packer, A. D. (Harlow : Longman, 1996)
A practical guide to the purpose and techniques of construction measurement, based on the current edition of the standard of measurement, SMM7. The introductory section identifies established practices in measurement including booking dimensions and documents production, and provides an overview of the new technologies associated with computer-based methods.
Essential reading for first and second year degree students following courses in quantity surveying, construction management, building and construction economics; it is also a useful tool for GNVQ and BTEC HNC/D building studies and surveying.
The book examines the principles of measurement and applies these techniques to a range of trades including substructures, external walls, structural floors, flat and pitched roofs, roof coverings, finishes, standard joinery, electrical/mechanical services and drainage installations.
0
Keywords: MCE -- Measurement